Clinical and biochemical characteristics of patients having general symptoms with increased serum IgG4. Issue 4 (3rd July 2020) - Hasegawa, Kou; Hanayama, Yoshihisa; Obika, Mikako; Miyoshi, Tomoko; Ogawa, Hiroko; Kondo, Eisei; Kataoka, Hitomi; Sato, Yasuharu; Otsuka, Fumio
Abstract: Objective: To differentiate patients with IgG4-related diseases (RD) from patients with other hyper IgG4 conditions who visit general medicine department. Methods: Fifty-six patients with high serum IgG4 levels (>135 mg/dL) were classified into three groups based on the final diagnosis: definite and possible IgG4-RD and others. Clinical and laboratory characteristics of the three groups of patients were retrospectively analyzed. Results: Major manifestations were renal dysfunction and general malaise, while thirst was the most frequent symptom in the definite group, in which submandibular glands and lymph nodes were likely to be affected. Biopsy of minor salivary glands was the least diagnostic for IgG4-RD despite the high frequency of biopsy. In the definite group, serum levels of IgG4 and IgG, IgG4/IgG ratio and basophil number were increased, while serum levels of CRP, IgA and complements were decreased. A negative correlation between serum levels of IgG4 and IgM was found in the definite group. Conclusion: The results indicated that in patients with renal dysfunction, malaise, thirst or weight loss, measurements of the levels of basophils, immunoglobulins and complements are helpful for diagnosing IgG4-RD. Considering distribution of affected tissues and localization of diagnostic biopsies, physical examination and laboratory workup are required for early diagnosis.